2010
DOI: 10.1002/ctpp.201010136
|View full text |Cite
|
Sign up to set email alerts
|

Short DC Discharge with Wall Probe as a Gas Analytical Detector

Abstract: A new approach leading to the development of gas analytical detectors is reported. The approach is based on measurements in the near-cathode plasma of fine structures associated with atomic and molecular plasma processes of the high energy portion of the electron energy distribution function (EEDF). A short (without positive column) dc discharge with cold cathode and conducting walls was used. The EEDF measurements in a dc discharge are technically simpler and have dramatically better sensitivity than in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…2,3 For atmospheric pressures, it is found that λ ε ≈ 100 μm and L < λ ε for typical microdischarges. The short dc discharges, including microdischarges, can be used, for instance, for plasma-chemical and surface modification applications, 7 as well as, for light sources, 8 analytical sensors, 9,10 and plasma electronic devices. 11 In contrast to semiconductor devices, plasma discharges can be used under harsh conditions related, for example, to high temperatures and radiation levels of damaged nuclear plants (such as Fukushima-like disasters).…”
mentioning
confidence: 99%
“…2,3 For atmospheric pressures, it is found that λ ε ≈ 100 μm and L < λ ε for typical microdischarges. The short dc discharges, including microdischarges, can be used, for instance, for plasma-chemical and surface modification applications, 7 as well as, for light sources, 8 analytical sensors, 9,10 and plasma electronic devices. 11 In contrast to semiconductor devices, plasma discharges can be used under harsh conditions related, for example, to high temperatures and radiation levels of damaged nuclear plants (such as Fukushima-like disasters).…”
mentioning
confidence: 99%